2016
DOI: 10.1097/iae.0000000000001159
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography of Choroidal Neovascularization in Four Inherited Retinal Dystrophies

Abstract: Purpose To demonstrate the clinical utility of optical coherence tomography (OCT) angiography (OCT-A) in inherited retinal dystrophies (IRDs) complicated by choroidal neovascularization (CNV). Methods OCT-A and structural OCT were performed using a 70 kHz spectral-domain OCT system employing the split-spectrum amplitude-decorrelation angiography algorithm. Semiautomated image processing software was used to segment and measure the CNV. Results Four participants were enrolled to study the following IRDs com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] MNV has been previously described as a possible complication, especially in the early stages of VMD. 1,2,[10][11][12][13]25,26 In most cases, exudative manifestations due to MNV activity have been treated with anti-VEGF intravitreal injections, with positive outcomes. 11,25,26 The present study, based on OCTA assessment, revealed that MNV is actually a quite frequent manifestation of VMD, occurring in about two-thirds of cases overall.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] MNV has been previously described as a possible complication, especially in the early stages of VMD. 1,2,[10][11][12][13]25,26 In most cases, exudative manifestations due to MNV activity have been treated with anti-VEGF intravitreal injections, with positive outcomes. 11,25,26 The present study, based on OCTA assessment, revealed that MNV is actually a quite frequent manifestation of VMD, occurring in about two-thirds of cases overall.…”
Section: Discussionmentioning
confidence: 99%
“…In later stages of CHM, choroidal neovascularization can develop, which can be difficult to detect on conventional angiogram. Patel et al demonstrated OCTA evidence of CNV with high flow signal in sub-RPE fibrovascular tissue [50]. Given the rarity of this disease and somewhat contradictory results in some of the above studies, additional OCTA studies enrolling larger number of patients are needed.…”
Section: Octa In Choroideremiamentioning
confidence: 99%
“…A different take on the amplitude decorrelation techniques consists of analyzing the properties of the members of the ensemble in Eqs. (8) and (9) instead of taking the ensemble average. This is in essence the principal component analysis (PCA) presented by Mohan et al [54] Experiments on phantoms showed the potential for flow velocity quantification of this method with a reduced number of data points.…”
Section: Intensity: Speckle Decorrelationmentioning
confidence: 99%
“…Recently, OCTA became commercially available as a tool for qualitative, non-invasive, 3D visualization of the blood vessel network of the posterior eye. In research studies as well as in the daily clinical routine, OCTA is on the way to becoming an accepted imaging modality for the diagnosis of retinal vascular disorders including neovascularization [8,9] and retinal vein occlusion [10]. Current clinical implementations of OCTA provide an almost binary discrimination between static tissue and blood vessels with sufficient flow, and a very limited ability for flow velocity quantification.…”
Section: Introductionmentioning
confidence: 99%